A battlefield of memory: the Nakba and the Holocaust as exclusive victimhood narratives - Wermenbol, G (2017)
Situated in the post-Oslo era, this work constitutes a parallel analysis of the collective transmission of the foundational pasts in Israeli-Jewish and Palestinian society, respectively the Holocaust and the Nakba. Through the application of postmodern criticism to Maurice Halbwachs’ unitary understanding of group memory transmission, this thesis exposes the existence and perpetuation of exclusive and ethnocentric victimhood narratives that provide the theoretical foundations for an ensuing minimization of the out-group’s past. Divided into three sections, which correspond to the examined realms of memory transmission, a range of qualitative research methods are used to analyze the conveyed narrative across the established realms of collective memory transmission: official state education, commemorative acts and mass mediation. Beyond an analysis of the depiction of the primary history events in the societies’ curricula, mass media and commemorative institutes, semi-structured interviews with (former) memory agents and participant observation testify to the interplay between elites’ historical conceptions and the transmitted narrative. While illustrating the universal plasticity of memory construction in coherence with contemporary political and societal needs, this work emphasizes the effects of the intractable Israeli-Palestinian conflict on the contemporary contextualization of the primary historical events and the ensuing subversion of the other’s past. Much like the original scenes of the watersheds and the principal actors, this thesis demonstrates that the exclusionary bases of Palestinian and Israeli victimhood narratives differ. The invocation of an exclusive Jewish Holocaust suffering thus is not unique to Israeli society; nevertheless, a consistent framing of a particularistic Zionist Holocaust victimhood narrative in the context of the Middle East conflict has stymied acknowledgement of the Palestinian catastrophe, deemed an inherent challenge to the ongoing redemptive nature of the Israeli state. An exclusive Palestinian victimhood narrative, conversely, has materialized in direct response to the opponent’s foundational memory. Rather than solely underlining an understanding of Israeli-Jewish political usage of the Holocaust, this thesis reveals that the retaliatory nature that characterizes the exclusive Palestinian narrative derives from its application as an interpretative framework –– an ‘ongoing Nakba’ –– which sheds light on the Palestinians’ marginalization and, consequently, demands a screening out of any past suffering of those held responsible.